Prioritization of the Criteria Affecting the Health of Elderly Women in Iran by Analytical Hierarchy Process (AHP) - Soodabeh Tayeri; Mehrnoosh Jafari; Khalil Ali Mohammadzadeh; Seyed Mojtaba Hosseini; Kamran Shahanaghi (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives With increasing life expectancy, aging in Iran becomes more feminine. This study aimed to prioritize the criteria affecting the health of Iranian elderly women. Methods & Materials In this descriptive-analytical study, factors affecting the health of the elderly women, with the opinion of 20 health-policy and health services management experts employed in governmental and non-governmental organizations, were approved. In the second phase, the weight and rank of these criteria were calculated and analyzed using Hierarchical Analysis Process. Excel software was used to analyze data. Results The analysis showed that the individual factor is the most important in terms of factors affecting the health of elderly women. In terms of the type of interventions, the provision of preventive health services, in terms of decision-making, executive interventions at the queue level, in terms of planning, integrated approach, and continuous planning with the participation of public and private sectors were ranked first. Conclusion Given the influence of the previous periods of life on healthy elderly, decision-makers should prioritize preventive services in all periods of life regarding age and gender context. Interventions should be presented with an integrated approach with continuous planning at the levels of government, organization, and queue, as well as with the participation of both public and private sectors. The existence of an information management system, supervision, and evaluation, provides the ground for continuous feedback and improvement of programs. Therefore, it is recommended that the government play a more significant role in ensuring the health of the elderly.